Acute kidney injury due to gentamicin nephrotoxicity and specific miRNAs as biomarkers - Klementa, Viktor; Petejová, Naděžda; Horák, Pavel; Kurašová, Ester; Zadražil, Josef (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2025)
Acute kidney injury (AKI) due to gentamicin nephrotoxicity is a significant concern in clinical medicine, particularly in patients receiving prolonged or high-dose gentamicin therapy. Gentamicin is an aminoglycoside antibiotic frequently used in the treatment of a range of bacterial infections. However, its use is associated with nephrotoxicity which can manifest as AKI. Due to this, it is crucial to diagnose promptly and manage treatment effectively. Ongoing studies are therefore focusing on non-protein-coding RNAs as potential biomarkers for AKI. Numerous microRNAs (miRNAs) have been implicated in gentamicin-induced nephrotoxicity and AKI. They participate in pathways associated with inflammation, cell death, and oxidative stress and each of these factors play critical roles in the development of gentamicin-induced kidney injury. Research studies have demonstrated changes in the expression levels of these miRNAs in response to gentamicin exposure both in vitro and in in vivo models, as well as in human clinical trials involving patients receiving gentamicin therapy. The dysregulation of these miRNAs correlates with the severity of kidney injury and may serve as sensitive biomarkers for early detection and monitoring of AKI induced by gentamicin.
Keywords: gentamiciny; mikro RNA; Acute Kidney Injury; Humans; biologické markery; Anti-Bacterial Agents; lidé; akutní poškození ledvin; antibakteriální látky; Biomarkers; Gentamicins; MicroRNAs